PENGARUH PENAMBAHAN KAPASITAS RUANG TERMINAL KEBERANGKATAN DOMESTIK TERHADAP KUALITAS PELAYANAN PUBLIK DI BANDAR UDARA INTERNASIONAL SULTAN HASANUDDIN MAKASSAR - Muhammad Iman; Ika Fathin Resti Martanti (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
The addition of the capacity of the domestic departure terminal room greatly affects passengers in terms of the quality of services provided by the airport, which can be assessed by passengers, in terms of meeting the needs of passengers. Passengers will feel satisfied if their needs and desires have been met. The purpose of this study is 1) To determine the effect of increasing the capacity of the domestic departure terminal space on the quality of public services at Sultan Hasanuddin International Airport Makassar. 2) To find out how big the effect of increasing the capacity of the domestic departure terminal space on the quality of public services at Sultan Hasanuddin International Airport Makassar. This study employed a quantitative research method. The research approach used was inferential statistics. The instrument used in this study was a questionnaire. The number of samples was taken using the Slovin technique. The number of research respondents was as many as 100 passengers. The analysis used to answer the problem formulation was a simple linear regression analysis assisted by using the SPSS v.24.0 computer statistical application program. The results of this study indicate that there is an effect of increasing the capacity of the domestic departure terminal space on the quality of public services at Sultan Hasanuddin International Airport Makassar. This is evidenced by the significant value of 0.00. Besides the addition of the domestic departure terminal room capacity contributes to the quality of public services at Sultan Hasanuddin International Airport Makassar by 47.5%.